Antimony-doped tin oxide / polyether ether ketone conductive material for piston rings and method for producing same
Patent Information
- Application Number
- CN202310696854.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-13
AI Technical Summary
金属材料价格较贵且易氧化,导电稳定较差;炭黑是常用的导电填料,但树脂基复合材料中分散性较差,高强度和模量的碳纤维的导电效果受温度影响较大;石墨因具有层状结构,用作填料时易分层,对力学性能影响较大
[0019]本发明的有益效果在于:本发明中所述的ATO粉末和纳米氧化铝预先经过表面改性处理,以提高其在PEEK基体中的分散性,有效防止颗粒团聚。所述的ATO粉末有效改善抗静电性能,纳米氧化铝提高了耐磨性,二者协同作用,有效改善复合材料的整体性能,且价格适中,适合产业化生产,可以满足汽车压缩机零部件(活塞环等)使用需求。
Smart Images

Figure CN116675947B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive materials, and more particularly to an antistatic composite material for piston rings and its preparation method. Background Technology
[0002] In recent years, engineering plastics and their composites have been increasingly used in the automotive industry for the purpose of lightweight design, due to their advantages such as low density and good performance. They have also gradually expanded from interior and functional materials to exterior parts and structural components, demonstrating great potential to replace steel with plastics.
[0003] Polyetheretherketone (PEEK), a commonly used thermoplastic material, is widely used in defense, aerospace, electronics, energy, automotive, home appliances, and medical fields due to its chemical stability, moldability, and excellent heat resistance. However, the electrostatic effect caused by PEEK's insulating properties limits its application in certain fields, such as the composite materials used in automotive compressor piston rings, where static electricity easily accumulates in daily life. To prevent and eliminate the effects of static electricity and achieve antistatic properties, the best approach is to reduce the resistivity of the polymer material. Conductive / antistatic materials, which have the ability to conduct current and eliminate charge, combined with other modification methods, can enhance the various properties of PEEK, especially its mechanical properties, wear resistance, and heat resistance, making it suitable for use in special environments.
[0004] Generally, conductive fillers include metals (gold, silver, copper, aluminum), carbon materials (carbon black, carbon fiber, graphite), and metal oxides (tin oxide, tin oxide, titanium oxide), etc. Metal materials are expensive and easily oxidized, resulting in poor conductivity. Carbon black is a commonly used conductive filler, but its dispersibility in resin-based composites is poor. The conductivity of high-strength and high-modulus carbon fibers is greatly affected by temperature. Graphite, due to its layered structure, is prone to delamination when used as a filler, significantly impacting mechanical properties.
[0005] Tin dioxide is a wide bandgap n-type metal oxide semiconductor material. Pure tin oxide has a high density, is in an insulating state at room temperature, and has a high resistivity, making it difficult to meet the requirements for electrical performance. Furthermore, when directly filled into polymer-based materials, it is prone to agglomeration and has poor dispersibility, thus failing to fully utilize its conductivity properties. Summary of the Invention
[0006] To overcome the shortcomings of the prior art, the present invention provides a method for preparing antimony-doped tin oxide / polyether ether ketone conductive material for piston rings. The conductive material prepared by this method has advantages such as good conductivity, chemical resistance, weather resistance, mechanical properties and dimensional stability, and moderate cost.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings includes the following steps:
[0009] A. Surface modification treatment of nano-antimony-doped tin oxide powder and nano-alumina: They were pre-dried in a vacuum chamber at 120℃ for 3 hours. 100g of each powder was weighed and added to a wide-mouth bottle containing 500ml of anhydrous ethanol. The pH was adjusted to 9.5 with 5wt% ammonia solution, and the mixture was ultrasonically dispersed for 30 minutes. Then, it was transferred to a three-necked flask and placed in a constant temperature water bath at 70℃ with uniform stirring. After the stirring stabilized, 50ml of coupling agent solution was added. The mixture was reacted for 6 hours, then dried, subjected to Soxhlet extraction for 24 hours, and subsequently vacuum dried, finely ground, and stored. The coupling agent was dissolved in anhydrous ethanol at a volume ratio of 1:2 to obtain the coupling agent solution.
[0010] B.PEEK was dried at 120℃ for 3 hours;
[0011] C. Weigh the dried materials according to the mass ratio and mix them in a high-speed mixer; PEEK: 80-93 parts; Surface-modified nano-antimony doped tin oxide powder: 5-15 parts; Surface-modified nano-Al2O3: 2-5 parts;
[0012] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0013] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0014] In the above-mentioned method for preparing antimony-doped tin oxide / polyether ether ketone conductive materials for piston rings, the coupling agent is KH550 or KH560 silane coupling agent.
[0015] The above-mentioned method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings, wherein the nano-antimony-doped tin oxide powder has a purity of not less than 99.0%, a wavelength of 20-80 nm, and a specific surface area of 49 m². 2 / g; The nano-Al2O3 powder has a particle size of 10-20nm.
[0016] The above-mentioned method for preparing antimony-doped tin oxide / polyether ether ketone conductive material for piston rings comprises 85 parts of PEEK, 10 parts of surface-modified nano-antimony-doped tin oxide powder, and 5 parts of surface-modified nano-Al2O3.
[0017] This invention also provides an antimony-doped tin oxide / polyetheretherketone conductive material for piston rings, which has good conductivity, chemical resistance, weather resistance, mechanical properties, high dimensional stability, and moderate cost, and is prepared according to the aforementioned preparation method.
[0018] This invention also provides an antimony-doped tin oxide / polyetheretherketone conductive material for piston rings, exhibiting good conductivity, chemical resistance, weather resistance, mechanical properties, high dimensional stability, and moderate cost. The material is composed of the following raw materials by weight percentage: PEEK: 80-93 parts, nano-antimony-doped tin oxide powder: 5-15 parts, and nano-Al₂O₃: 2-5 parts; wherein the nano-antimony-doped tin oxide powder and nano-Al₂O₃ are surface-activated using a silane coupling agent. Preferably, the nano-antimony-doped tin oxide powder has a purity of 99.0%, a wavelength of 20-80 nm, and a specific surface area of 49 m². 2 / g. Preferably, the nano-Al2O3 has a particle size of 10-20nm.
[0019] The beneficial effects of this invention are as follows: The ATO powder and nano-alumina described in this invention undergo surface modification treatment beforehand to improve their dispersibility in the PEEK matrix and effectively prevent particle agglomeration. The ATO powder effectively improves antistatic properties, while the nano-alumina enhances wear resistance. The synergistic effect of the two effectively improves the overall performance of the composite material, and the price is moderate, making it suitable for industrial production and meeting the needs of automotive compressor parts (piston rings, etc.).
[0020] Modifying antimony-doped tin oxide (ATO) conductive powder and filling it into the PEEK matrix material effectively improves its dispersibility in the substrate and prevents nanoparticle agglomeration.
[0021] ATO conductive powder is added to PEEK resin matrix to give it good conductivity and chemical stability. When used in piston rings of automotive compressor parts, it reduces static electricity accumulation and has a better antistatic effect.
[0022] The synergistic effect of nano-Al2O3 powder and ATO conductive powder further improves the wear resistance and mechanical properties of the composite material. Attached Figure Description
[0023] Figure 1 The image shows the EDS composition analysis SEM image of the conductive material prepared in Example 4 of this invention.
[0024] Figure 2 For the present invention Figure 1 The energy spectrum in the image. Detailed Implementation
[0025] To clearly illustrate the content of this invention and enable those skilled in the art to implement it, the following examples are provided, but the invention is not limited to these examples.
[0026] PEEK, in powder form, with a particle size of 100-260nm, was purchased from Victrex, UK.
[0027] ATO powder, in powder form, with a purity of 99.5%, purchased from Shanghai Huzheng Nanotechnology Co., Ltd.
[0028] Nano-Al2O3 with a particle size of 10-20nm was purchased from Nanjing Baoket New Materials Co., Ltd.
[0029] The test methods used in Embodiments 1-5 and Comparative Examples 1-2 of the present invention are as follows:
[0030] Mechanical property testing: Tensile properties were tested according to ASTM D4745, at a room temperature of 23±2℃, an ambient humidity of 50%RH, and a test speed of 50mm / min.
[0031] Friction and wear performance: Tested according to GB 3960—2016. Before the test, the surface was polished with 1200-grit metallographic sandpaper. The test conditions were: positive load 196N, friction torque 5N·m, rotation speed 200r / min, test time 120min, dry friction, room temperature 23±2℃.
[0032] Electrical performance conforms to GB / T 1410-2006 / IEC 60093:1980. Test environment: temperature 23±2℃, relative humidity RH≤75%, conductive electrode: copper plate, insulating pad: marble table.
[0033] Example 1
[0034] A. Surface modification treatment of antimony-doped tin oxide powder and nano-alumina: First, antimony-doped tin oxide powder (or nano-alumina) was pre-dried in a vacuum chamber at 120℃ for 3 hours. 100g was weighed and added to a wide-mouth bottle containing 500ml of anhydrous ethanol. The pH was adjusted to 9.5 with 5wt% ammonia solution, and the mixture was ultrasonically dispersed for 30 minutes. Then, it was transferred to a 1000ml three-necked flask and placed in a constant temperature water bath at 70℃ with uniform stirring. After the stirring was stable, 50ml of coupling agent solution (coupling agent KH560 dissolved in anhydrous ethanol at a volume ratio of 1:2) was added through a dropper from the bottle mouth. After reacting for 6 hours, the mixture was dried, Soxhlet extracted for 24 hours, then vacuum dried, ground, and stored.
[0035] B.PEEK was dried at 120℃ for 3 hours;
[0036] C. Weigh out 93 parts of PEEK, 5 parts of surface-modified ATO powder, and 2 parts of surface-modified alumina after drying, and mix them in a high-speed mixer.
[0037] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0038] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0039] Example 2
[0040] A. Surface modification treatment of nano-antimony-doped tin oxide powder and nano-alumina: First, nano-alumina (or nano-antimony-doped tin oxide powder) is pre-dried in a vacuum chamber at 120℃ for 3 hours. 100g is weighed and added to a wide-mouth bottle containing 500ml of anhydrous ethanol. The pH is adjusted to 9.5 with 5wt% ammonia solution, and ultrasonically dispersed for 30 minutes. Then, it is transferred to a 1000ml three-necked flask and placed in a constant temperature water bath at 70℃ with uniform stirring. After the stirring is stable, 50ml of coupling agent solution (coupling agent KH550 dissolved in anhydrous ethanol at a volume ratio of 1:2) is added through a dropper from the mouth of the bottle. After reacting for 6 hours, it is taken out and dried, Soxhlet extracted for 24 hours, then vacuum dried, ground, and stored.
[0041] B.PEEK was dried at 120℃ for 3 hours;
[0042] C. Weigh out 88 parts of PEEK, 10 parts of surface-modified ATO powder, and 2 parts of surface-modified alumina after drying, and mix them in a high-speed mixer.
[0043] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0044] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0045] Example 3
[0046] A. Surface modification treatment of nano-antimony-doped tin oxide powder and nano-alumina: First, pre-dry them separately in a vacuum chamber at 120℃ for 3 hours. Weigh 100g and add it to a wide-mouth bottle containing 500ml of anhydrous ethanol. Adjust the pH to 9.5 with 5wt% ammonia solution, and ultrasonically disperse for 30 minutes. Then transfer it to a 1000ml three-necked flask and place it in a constant temperature water bath at 70℃ with uniform stirring. After the stirring is stable, add 50ml of coupling agent solution (coupling agent KH560 dissolved in anhydrous ethanol at a volume ratio of 1:2) through a dropper from the bottle mouth. After reacting for 6 hours, take it out and dry it. Soxhlet extract for 24 hours, then vacuum dry, grind it finely, and store it.
[0047] B.PEEK was dried at 120℃ for 3 hours;
[0048] C. Weigh out 83 parts of PEEK, 15 parts of surface-modified ATO powder, and 2 parts of surface-modified alumina after drying, and mix them in a high-speed mixer.
[0049] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0050] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0051] Example 4
[0052] A. Surface modification treatment of nano-antimony-doped tin oxide powder and nano-alumina: First, pre-dry them separately in a vacuum chamber at 120℃ for 3 hours. Weigh 100g and add it to a wide-mouth bottle containing 500ml of anhydrous ethanol. Adjust the pH to 9.5 with 5wt% ammonia solution, and ultrasonically disperse for 30 minutes. Then transfer it to a 1000ml three-necked flask and place it in a constant temperature water bath at 70℃ with uniform stirring. After the stirring is stable, add 50ml of coupling agent solution (coupling agent KH550 dissolved in anhydrous ethanol at a volume ratio of 1:2) through a dropper from the bottle mouth. After reacting for 6 hours, take it out and dry it. Soxhlet extract for 24 hours, then vacuum dry, grind it finely, and store it.
[0053] B.PEEK was dried at 120℃ for 3 hours;
[0054] C. Weigh out 85 parts of PEEK, 10 parts of surface-modified ATO powder, and 5 parts of surface-modified alumina after drying, and mix them in a high-speed mixer.
[0055] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0056] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0057] Example 5
[0058] A. Surface modification treatment of nano-antimony-doped tin oxide powder and nano-alumina: First, pre-dry them separately in a vacuum chamber at 120℃ for 3 hours. Weigh 100g and add it to a wide-mouth bottle containing 500ml of anhydrous ethanol. Adjust the pH to 9.5 with 5wt% ammonia solution, and ultrasonically disperse for 30 minutes. Then transfer it to a 1000ml three-necked flask and place it in a constant temperature water bath at 70℃ with uniform stirring. After the stirring is stable, add 50ml of coupling agent solution (coupling agent KH560 dissolved in anhydrous ethanol at a volume ratio of 1:2) through a dropper from the bottle mouth. After reacting for 6 hours, take it out and dry it. Soxhlet extract for 24 hours, then vacuum dry, grind it finely, and store it.
[0059] B.PEEK was dried at 120℃ for 3 hours;
[0060] C. Weigh out 80 parts of PEEK, 15 parts of surface-modified ATO powder, and 5 parts of surface-modified alumina after drying, and mix them in a high-speed mixer.
[0061] D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold.
[0062] E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
[0063] The performance test results of the antimony-doped tin oxide / polyetheretherketone conductive materials for piston rings prepared in Examples 1-5 above are shown in Table 1.
[0064] Comparative Example 1
[0065] For comparison with this technical solution, the comparative example is counted by weight ratio: 100 parts of PEEK, and the other preparation methods are exactly the same as in Example 1. The performance test results are shown in Table 1.
[0066] Comparative Example 2
[0067] For comparison with this technical solution, the comparative example is calculated by weight ratio as follows: 97 parts PEEK, 3 parts surface-modified ATO powder, and the other preparation methods are exactly the same as in Example 1. The performance test results are shown in Table 1.
[0068] Table 1
[0069]
[0070] As can be seen from the above results, when ATO nanoparticles and nano-alumina particles fill PEEK substrates at an addition ratio of 10% and the addition amount of nano-alumina powder is 5%, the antimony-doped tin oxide / polyether ether ketone conductive material has advantages such as good antistatic properties, tensile properties, wear resistance, and moderate cost. Its application in automotive compressor parts (piston rings) can meet the performance requirements.
[0071] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. These are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings, characterized in that: Includes the following steps: A. Surface modification treatment of antimony-doped tin oxide powder and nano-alumina: Antimony-doped tin oxide powder and nano-alumina were pre-dried in a vacuum chamber at 120℃ for 3 hours. 100g of each powder was weighed and added to a wide-mouth bottle containing 500ml of anhydrous ethanol. The pH was adjusted to 9.5 with 5wt% ammonia solution, and the mixture was ultrasonically dispersed for 30 minutes. Then, the mixture was transferred to a three-necked flask and placed in a constant temperature water bath at 70℃ with uniform stirring. After the stirring was stable, 50ml of coupling agent solution was added. The mixture was reacted for 6 hours, dried, and subjected to Soxhlet extraction for 24 hours. Subsequently, it was vacuum dried, ground, and stored. The coupling agent was dissolved in anhydrous ethanol to obtain a coupling agent solution, wherein the volume ratio of coupling agent to anhydrous ethanol was 1:
2. B. PEEK was dried at 120℃ for 3 hours; C. Weigh the dried materials according to the mass ratio and mix them in a high-speed mixer; PEEK: 80-93 parts; Surface-modified nano-antimony doped tin oxide powder: 5-15 parts; Surface-modified nano-Al2O3: 2-5 parts; D. Place the mixed material into a hot press mold cavity at 380-395℃, and after melting, mold it under a pressure of 20MPa, then cool and demold. E. After demolding, the blank is kept at 180℃ for 2 hours and then naturally cooled to obtain the finished product.
2. The method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings according to claim 1, characterized in that: The coupling agent is KH550 or KH560 silane coupling agent.
3. The method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings according to claim 1, characterized in that: The nano-antimony-doped tin oxide powder has a purity of not less than 99.0%, a particle size of 20-80 nm, and a specific surface area of 49 m². 2 / g; the particle size of the nano Al2O3 powder is 10-20nm.
4. The method for preparing antimony-doped tin oxide / polyetheretherketone conductive material for piston rings according to claim 1, characterized in that: 85 parts of PEEK, 10 parts of surface-modified nano-antimony-doped tin oxide powder, and 5 parts of surface-modified nano-Al2O3.
5. The antimony-doped tin oxide / polyetheretherketone conductive material for piston rings prepared according to the preparation method of claim 1.
Citation Information
Patent Citations
Method for preparing ATO conductive powder using nano antimony oxide and tin oxide powder
CN101468397A
Low temperature and wear resisting PEEK composite material and preparation method thereof
CN105542389A
